Barriers and facilitators to using pain treatment during newborn screening blood tests at a mother-baby unit. Issue 3 (June 2019) - Lavin Venegas, Carolina; Taljaard, Monica; Reszel, Jessica; Harrison, Denise
Abstract: Background: Newborns undergo blood tests for newborn screening (NBS). Breastfeeding, skin-to-skin care (SSC) and sweet solutions effectively reduce pain; however, these strategies are inconsistently used. Aims: To assess the utilization of, and barriers and facilitators to using pain treatment during NBS. Methods: Online survey of nurses in a mother-baby unit ascertaining pain management during NBS, and barriers/facilitators to using the three strategies. Participants viewed a video portraying the use of each strategy during NBS. Results: Thirty-six of 45 nurses participated (response rate = 80%). Thirty-five (97%) reported completing NBS outside the patient's room. Breastfeeding was sometimes supported (44%) and 40% never suggested SSC, while 53% often used sucrose. After viewing the video, nurses preferred sucrose (mean = 82) over breastfeeding (mean = 44) or SSC (mean = 44). Main barriers to using breastfeeding and SSC were ergonomics, contextual factors and time. Conclusions: Further work is warranted to address barriers to using evidence-based pain treatment for newborns during NBS.